Habitabilidade na cidade sobre as águas: desafios da implantação de infra-estrutura de saneamento nas palafitas do Igarapé do Quarenta bairro Japiim Manaus/AM - Almeida, Larissa Christinne Melo de (2005)
The present research if inserts in the subject of the habitation of social interest and its relation with the sanitation infra-structure questions (sewer, water, draining and garbage). Having as study universe the narrow river of the Forty , situated one in the city of Manaus, capital of Amazon, approaches questions that if present between the necessities of housing and the especificidades of the natural environment, whose characteristics evidence limits for the implantation of adequate habitations. The objective is to analyze the possibilities and the limits of the urbanística regularization in the palafitas of the narrow rivers of Manaus, in view of the factors of habitability and ambient protection, expresses for the sanitation system - sanitary exhaustion, water supply, urban draining and garbage collection. The work approaches initially relative the conceptual aspects to the subject of social habitation in the country and its relation with the habitability factors, also focusing the question of the housing and the processes of urban informality in the city of Manaus. It deals with the process of constitution of the palafitas in the space of the city and its relation with the habitacionais politics, presenting the analysis of the implantation of the palafitas in relation to the sanitation infra-structure conditions (sewer, water, draining and garbage). As conclusion, it identifies to the possibilities and limits of urbanística regularization of the palafitas implanted to the long one of the narrow river of the Forty , taking in consideration the systems of the sanitation infrastructure